Negotiating Femininity and Masculinity: A Judith Butler Approach to Megan Trainor’s 'Dear Future Husband' - Ria Saraswati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study employs Judith Butler’s theory of gender performativity to analyze Megan Trainor’s song